2022
DOI: 10.1371/journal.pone.0277426
|View full text |Cite
|
Sign up to set email alerts
|

Universal admission screening for COVID-19 using quantitative antigen testing and questionnaire screening to prevent nosocomial spread

Abstract: Background In this study, we investigated diagnostic accuracy of quantitative severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antigen testing and whether universal screening was effective to prevent a nosocomial outbreak of coronavirus disease 2019 (COVID-19). Methods All adult patients admitted to an acute-care hospital in Tokyo, Japan, after receiving LUMIPULSE SARS-CoV-2 Ag using a nasopharyngeal swab and a brief questionnaire to evaluate symptoms and exposures from December 3, 2020 to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Ten of these cases (0.76% of total tests) were diagnosed as acute-phase COVID-19. Previous studies at other Japanese hospitals have reported 0.07% to 1.81% SARS-CoV-2 positivity for routine screening tests [ 6 - 8 ]. Our PCR positivity rate (0.76%) is thus similar to that of other Japanese studies conducted before the omicron variant outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of these cases (0.76% of total tests) were diagnosed as acute-phase COVID-19. Previous studies at other Japanese hospitals have reported 0.07% to 1.81% SARS-CoV-2 positivity for routine screening tests [ 6 - 8 ]. Our PCR positivity rate (0.76%) is thus similar to that of other Japanese studies conducted before the omicron variant outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Measures to prevent SARS-CoV-2 infection in hospitals include patient and staff screening, hand hygiene, isolation of patients with a suspected infection, and vaccination [ 5 ]. Among these measures, screening of patients on admission by polymerase chain reaction (PCR) [ 6 , 7 ] or antigen [ 8 , 9 ] tests has been found to be particularly effective. It can be difficult to diagnose COVID-19 on the basis of symptoms alone among individuals with other respiratory diseases, given the similarity in symptoms between these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…5 Data from previous research has shown the detection of SARS-CoV-2 with RAT compared to RT-PCR. 6,7 There are certain pitfalls in using RAT like most of the kits require nasopharyngeal swab which is quite difficult to collect in pediatric age group and in mentally challenged individuals, a meta analysis study shown an average sensitivity and specificity of RAT as 56.2% and 99.5% respectively. 8 There are various RAT kits approved by ICMR for the diagnostic use.…”
Section: Introductionmentioning
confidence: 99%